ORAL ADMINISTRATION OF PEPPERMINT IN WISTAR ALBINO RATS: Memory Boosting and Regaining - Jasira, M.; Sai-Sailesh, K.; Mukkadan, and J. K. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2013)
The studies on peppermint aroma fluence on cognition are numerous. However the knowledge about oral consumption of peppermint and cognition was inadequate. Hence the present study was undertaken to find out the effect of oral administration of peppermint spices in memory boosting and memory regaining on adult wistar rats. Here we investigate the influence of oral intake of peppermint on behavioral task performance by using T-maze and radial arm maze and physiological measures relative to a milk control group. We have observed significant memory boosting and memory regaining effects of peppermint when administered orally. This effect may be due to improvement of the blood flow to the brain and increasing the concentration power.  Hence we recommend further research in this area by investigating compound metabolism to optimize quantification of memory performance following peppermint ingestion.
Keywords: Memory boosting, Memory retention, peppermint ingestion.